Exploring the Impact of Broken Home Conditions on Adolescents' Focus and Academic Achievement - Sarnoto, Ahmad Zain; Sari , Windy Dian; Alhan, Khusni; Hidayat, Rachmat; Saksitha, Deassy Arestya (PELNUS | Pen en Light for Natural Union of Science, 2024)
The prevalence of broken homes, characterized by parental separation, divorce, or single-parent households, poses significant challenges to adolescents' development and academic outcomes. This research explores the intricate relationship. Through a mixed-methods approach encompassing quantitative surveys and qualitative interviews, the study examines the mechanisms through which family disruptions influence academic functioning among adolescents. Quantitative analyses reveal significant associations between broken home conditions and lower levels of attentional control, task persistence, and academic engagement among adolescents. These findings persist even after controlling for demographic variables such as socioeconomic status and parental involvement, underscoring the independent contribution of family disruptions to academic outcomes. Qualitative insights provide rich contextual understanding of the lived experiences of adolescents in broken homes, highlighting the emotional turmoil, insecurity, and challenges they face in navigating academic demands amidst familial upheaval. The implications of these findings are far-reaching, with significant implications for educational practice, policy, and intervention efforts. By recognizing the unique needs of adolescents from broken homes and developing evidence-based strategies to support their holistic development and academic success, educators, policymakers, and stakeholders can create nurturing and inclusive environments where all adolescents have the opportunity to thrive.